CONTRIBUTIONS OF THE GATT/WTO TO GLOBAL ECONOMIC WELFARE: EMPIRICAL EVIDENCE. (27th August 2014) - Anderson, Kym
Abstract: This paper surveys estimates of the value of the GATT/WTO's contributions to global welfare through providing a forum for negotiating reductions in policy‐induced distortions to trade flows, including through the process of accession by new members. After reviewing measures of the price‐distorting effects of trade‐related policies, it assesses estimates from global simulation models of the welfare effects of trade liberalizations prior to the WTO's Doha round, including the net benefits and transfers associated with implementing the Uruguay Round agreement on trade‐related intellectual property rights, and then reviews estimates of the potential welfare effects of a Doha round agreement to cut tariffs and subsidies. Econometric estimates of past trade and related effects of the GATT/WTO are then examined, before turning to estimates of the benefits of WTO accession and of potential benefits from WTO‐sponsored trade facilitation. The paper concludes that while it remains difficult to attribute reforms directly to the GATT/WTO, the overall body of evidence presented supports the economic profession's consensus that this institution has contributed substantially to global economic welfare.